2015
DOI: 10.1136/annrheumdis-2014-206847
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid hyaluronan mediates MSC attachment to cartilage, a potential novel mechanism contributing to cartilage repair in osteoarthritis using knee joint distraction

Abstract: ObjectivesKnee joint distraction (KJD) is a novel, but poorly understood, treatment for osteoarthritis (OA) associated with remarkable ‘spontaneous’ cartilage repair in which resident synovial fluid (SF) multipotential mesenchymal stromal cells (MSCs) may play a role. We hypothesised that SF hyaluronic acid (HA) inhibited the initial interaction between MSCs and cartilage, a key first step to integration, and postulate that KJD environment favoured MSC/cartilage interactions.MethodsAttachment of dual-labelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 50 publications
(71 reference statements)
2
72
0
Order By: Relevance
“…Since SF-MSCs have the advantage of direct access to the site of injury without the need to breach the subchondral plate [36], combining PL with SF-MSCs might be relevant for early cartilage repair. Our results showed that PL maintained the in vitro phenotype in agreement with the recommendation of the ISCT [37].…”
Section: Discussionmentioning
confidence: 99%
“…Since SF-MSCs have the advantage of direct access to the site of injury without the need to breach the subchondral plate [36], combining PL with SF-MSCs might be relevant for early cartilage repair. Our results showed that PL maintained the in vitro phenotype in agreement with the recommendation of the ISCT [37].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is still no curative treatment for KOA and only a small number of limited treatments, which aim to reduce pain and control inflammation to improve function. The treatment of KOA in the early stages includes physical therapy, [4][5][6] pain relief by nonsteroidal anti-inflammatory drugs, 7 cell-based therapy, 8,9 and intra-articular injection of hyaluronan or corticosteroids. 10 However, these therapies provide only temporary clinical symptom relief and do not restore cartilaginous, meniscal, and ligamentous function.…”
Section: See Commentary On Page 660mentioning
confidence: 99%
“…These studies suggest that, by temporarily offloading the joint, KJD might somehow be responsible for 'priming' the joint to enable intrinsic cartilaginous repair. The biological mechanisms which underlie such a response are not understood but may include changes in the peri-articular bone and enhanced mesenchymal stem cell attachment to the damaged joint surface 19,20 . KJD is therefore an attractive mechanistic model in which to investigate potential reparative pathways and identify novel associated markers of clinical response.…”
Section: Introductionmentioning
confidence: 99%